2023
DOI: 10.3390/plants12061355
|View full text |Cite
|
Sign up to set email alerts
|

Hydroponic and Aquaponic Floating Raft Systems Elicit Differential Growth and Quality Responses to Consecutive Cuts of Basil Crop

Abstract: Basil crops are appreciated for their distinct flavour and appeal to various cuisines globally. Basil production is mainly implemented in controlled environment agriculture (CEA) systems. Soil-less cultivation (e.g., hydroponic) is optimal for producing basil, while aquaponics is another technique suitable for leafy crops such as basil. Shortening the production chain through efficient cultivation techniques reduces basil production’s carbon footprint. While the organoleptic quality of basil demonstrably benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…From each trough, 5 individuals were separated for the determination of leaf areas. The samples were photographed from a vertical view to make measurements of leave areas using the Image J software program (US National Institutes of Health) (Modarelli et al, 2023). Atmospheric parameters that are directly related to plant growth are obtained from the closest weather station.…”
Section: Plant Growthmentioning
confidence: 99%
“…From each trough, 5 individuals were separated for the determination of leaf areas. The samples were photographed from a vertical view to make measurements of leave areas using the Image J software program (US National Institutes of Health) (Modarelli et al, 2023). Atmospheric parameters that are directly related to plant growth are obtained from the closest weather station.…”
Section: Plant Growthmentioning
confidence: 99%
“…Cruz et al [12] suggested connecting and managing the smart farming system using the Internet of Things platform for smart strawberry farming. Modarelli et al [13] proposed that aquaponics is suitable for leafy crops such as basil (Ocimum basilicum) due to the reduced utilization Plants 2024, 13, 463 2 of 13 of chemical fertilizers and increased productivity. Kim et al [14] reported that treating one-year-old ginseng with light-emitting diodes (LEDs) increased the weight of shoots in the cultivation chamber.…”
Section: Introductionmentioning
confidence: 99%